Self-reported or register-based? A comparison of sickness absence data among 8110 public and private employees in Denmark - Sannie V Thorsen; Mari-Ann Flyvholm; Ute Bültmann (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: The study aim was to examine (i) non-response bias between responders and non-responders, and (ii) whether the association between self-reported sickness absence (SA) and register-based SA differed by gender, age, sector, or physically demanding work. METHODS: The responses of 8110 participants to a question on self-reported SA in past 12 months in the Work Environment and Health in Denmark Survey (2014) was linked to 12 months of SA data from the Danish Register of Work Absence. We used logistic regression for the non-response analysis and Poisson regression to examine associations. RESULTS: Responders had on average 0.5 days less SA per year than non-responders. Public employees had a higher response rate than private employees (approximately five percentage points), women had a higher rate than men (approximately nine percentage points), and older employees a higher rate than younger employees (approximately nine percentage points in ten years). Self-reported SA correlated highly with register-based SA (Spearman's rank correlation=0.76). In general, responders with few SA days (<10) under-reported their SA while responders with many SA days (>30) over-reported their SA. Women under-reported significantly more than men (average difference one day); older employees under-reported significantly more than younger employees (difference between age groups 18-29 and 60-64 was 1.7 days). Differences between sectors or levels of physically demanding work were non-significant. CONCLUSIONS: Self-reported SA data may be influenced by non-response bias, and different accuracy in different demographic groups. When available, the use of register-based SA data is recommended.